Integrated Production Optimization of Mature Field Y Under Network Constraints - Steven Chandra; Brian Tony; Rahma Widyastuti (Journal of Petroleum and Geothermal Technology, 2023)
The Y Field, a mature field experiencing declining reservoir pressure, the production of hydrocarbons is declining, leading to the need for production optimization. One crucial aspect of this optimization is the selection of suitable artificial lift methods. The choice of artificial lift methods in Field Y is dependent on the unique reservoir conditions of each well. The commonly utilized equipment for artificial lift methods in Field Y includes the Sucker Rod Pump (SRP) and the Electrical Submersible Pump (ESP).This bachelor thesis aims to develop an integrated production optimization strategy for maximizing well production in Structure X, a mature field. The study involves analyzing and optimizing artificial lift methods and integrating surface network simulation. The Inflow Performance Rate (IPR) curve is utilized to identify the production potential of each well in Structure X.By evaluating the pump performance and surface network in Structure X, it is possible to identify wells that utilize artificial lift or existing pumps and have the potential to be improved up to their maximum operating range, based on their gross flow rate (BFPD). Through optimization, adjusting the stroke per minute for the Sucker Rod Pump (SRP) and the operating frequency for the Electrical Submersible Pump (ESP) can lead to a significant increase in production. Specifically, with a design production rate of 2308.59 BFPD, an improvement of 82.23 BOPD can be achieved.